A “near miss" congenital eventration of the right hemidiaphragm in a neonate: a case report - Zainudin, Zurina; Syed Abdullah, Farah Inaz; Neoh, Siew Hong; Bahari @ Mohd Fakhruddin, Mughni; Cheah, Irene Guat Sim (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Focal eventration involving the posterior segment of the hemidiaphragm is a rare congenital anomaly. We report of a 10-day-old infant who presented with significant respiratory insufficiency and failure to show any responses to standard treatment. The diagnosis of focal eventration of the diaphragm was not anticipated until ultrasonographic examination revealed the defect. Diaphragmatic plication resulted in complete resolution of symptoms. A high level clinical awareness is crucial as a relatively simple surgical procedure could avert long term life-threatening complications.